A prospective study of relationship of vascular pedicle width with Cardiothoracic Ratio, Hemodynamic Data and Pulmonary Edema in Vertilated Intensive Care Unit patients - Lukman, Mohd Fahmi; Yahaya, Azura Sharena; Osman, Ariff (2009)

(untitled)
In order to explore problems facing by local Small Medium Enterprises (SMEs) in adopting Enterprise Resource Planning (ERP) systems, this paper seeks to investigate what are the barriers to ERP system adoption by SMEs? The research was conducted in a Malaysian medium-sized company that planned to adopt ERP systems. Prior researches have identified that high cost; lack of knowledge; highly centralized structure; and issue of misfit to be barriers to ERP adoption by SMEs. From the case study, apart from the previous mentioned factors, the company has to do without a project champion and influenced by the perceived risk associated ERP systems implementation. Limitation of the research is that it was based on a single-case study, imposes care in generalizing the results of the study. This research, however, allows the identification and understanding of barriers to ERP adoption in local setting.